ChemInform Abstract: Iron(II)‐Catalyzed Intramolecular Olefin Aminofluorination. Issue 48 (2nd December 2014) - Lu, Deng‐Fu; Liu, Guan‐Sai; Zhu, Cheng‐Liang; Yuan, Bo; Xu, Hao
Abstract A novel Fe(II)‐catalyzed diastereoselective olefin aminofluorination to transform allylic alcohol derivatives to side chain fluorinated oxazolidinones is developed.